Deficits in naming and auditory comprehension of terms in individuals with vascular dementia - Vasilijević, Slavica; Vuković, Mile (Vojnosanitetski pregled, 2025)
Background/Aim. Although deficits in naming and understanding named terms are characteristic of dementia, they have seldom been investigated in individuals with vascular dementia (VaD). The aim of the study was to determine deficits in naming objects and actions in individuals with VaD and the ability to understand the meanings of words used to name objects and actions. Methods. The study included 30 participants with VaD, who represented the clinical group, while the control group consisted of 30 neurologically healthy participants. Participants with VaD were first assessed using the Mini-Mental State Examination to determine the severity of dementia. The Northwestern Naming Battery was used to assess naming and auditory comprehension of terms. Descriptive and inferential statistical methods were used for data analysis. Group comparisons were conducted using the Chi-squared (χ2) test of independence, while for 2 × 2 contingency frequency tables, continuity correction according to Yates was applied, and the phi (ϕ) coefficient was calculated as an indicator of effect size. The relationships between continuous variables were expressed using Spearman’s rank correlation coefficient rho (ρ). Results. Participants with VaD demonstrated significantly lower performance on the subtest of naming and auditory comprehension of named objects and actions compared to neurologically healthy participants. The severity of dementia significantly influenced the performance on the administered test. Specifically, participants with moderate dementia exhibited significantly lower scores on all subtests of naming and comprehension of named objects compared to participants with milder dementia. Conclusion. Individuals with VaD exhibit pronounced deficits in naming and understanding named terms. The ability to name and understand named terms significantly declines with the progression of dementia.